Mesozoic deformation of the Nadanhada Terrane (NE China) and its implications on the subduction of the Paleo-Pacific Plate. (1st July 2022) - Lan, Haoyuan; Li, Sanzhong; Guo, Lingli; Li, Xiyao; Liu, Yongjiang; Liu, Bo; Santosh, M.; Cao, Xianzhi; Zhang, Ruixin; Wang, Guangzeng
Graphical abstract: Highlights: The Nadanhada Terrane underwent four-stage deformation in the Mesozoic. The accretion of oceanic seamounts resulted in the curved fold-and-thrust belt. The subduction of a massif possibly made the Nadanhada Terrane preserved. Abstract: The Nadanhada Terrane in Northeast China preserves important imprints of Mesozoic tectonic events and is therefore a key area to explore the evolutionary process of the Paleo-Pacific Plate along the northwestern Pacific continental margin. Here we present new results from detailed structural analysis of the Nadanhada Terrane. We also synthesize the previously published data from geochronology, geochemistry, petrology, paleobiology and paleomagnetism. The structural analysis reveals four-stage deformation in the Nadanhada area from late Early Jurassic to early Late Cretaceous. The first-stage deformation is represented by the ENE-striking tight folds or NNW-dipping schistosity during the late Early Jurassic, reflecting the northwestward subduction of the Paleo-Pacific Plate. The second-stage deformation occurred during the earliest Cretaceous and is characterized by chevron or asymmetric folds with some thrust faults, with varying strikes, and the regional structural lines indicate westward-protruding arcs in the plan view. The westward-protruding structural trend lines are probably caused by the combined influence of the difficultly-deformed Jurassic volcanic arcs in the south and the coevally-accreted seamounts in the middle. There was likely a small massif, probably the Pre-Nadanhada Massif, subducted and then stagnated beneath the Nadanhada Terrane later than this process, making the Nadanhada Terrane better preserved. The third-stage deformation is represented by some late Early Cretaceous top-to-the SW thrusts, which is likely related to the closure of the Mongol-Okhotsk Ocean. The fourth-stage deformation is characterized by NE-trending thrust faults with some fault-related folds in the early Late Cretaceous, indicating another stage of intense northwestward subduction of the Paleo-Pacific Plate.